HUBUNGAN PENGETAHUAN TENTANG ZAT ADITIF DENGAN SIKAP PEMILIHAN MAKANAN JAJANAN SISWA SMPN 74 JAKARTA - Rahayu, Sri; Refirman, R; Sari, Dewi Ratna (Universitas Negeri Jakarta, 2016)
The junior high school students almost every day activities of the school to get an extra snack energy after a long day at school. However, snack food in schools and surrounding areas can not be secured, including the safety of additives. To avoid students from the negative impact of food additives, the needed knowledge about the additives. Knowledge of these additives have an important role in shaping the attitude of the selection of snack food. This study aim to determine correlation between knowledge of additives and attitude about selection of snack food students at SMPN 74 Jakarta. The research was conducted at SMPN 74 Jakarta on April-May 2016. The method of this study was descriptive method with survey techniques through correlational studies. The sample of this study was 166 students. Prerequisite test results showed that the data was normally distributed and homogeneous. Regression model Å¶= 127.35 + 2.23X that was significant and had a linear correlation. Based on hypothesis testing, the value of the correlation coefficient of 0.76 and a coefficient of determination of 58%. Based on these results, it can be concluded that there was a positive correlation between knowledge about additives and attitude about selection of snack food students at SMPN 74 Jakarta and knowledge about additives contributed 58% to attitude about selection of snack food students at SMPN 74 Jakarta.